Specialization and business cycles fluctuations of Polish regions - Warżała, Rafał (Managerial Economics, 2016)
The aim of this article is to investigate the relationship between the cyclical fluctuations in Poland on a regional perspective and the level of specialization of regional economies. To do this, the correlation between the morphology features of regional business cycles and the level of their specialization was made. The morphology features were represented by such parameters: cycle length, phase length, standard deviation ratio, coefficient of variation ratio and average amplitude of upward and downward phases. The evolution of economic structures was measured by the Krugman specialization index. Assessing the GDP cyclical fluctuations in the Polish regions during 1996–2013, it can be concluded that the regions have different sensitivity to economy “shocks,” both positive and negative. The results of the regional specialization measuring are ambiguous. Most of them appear falling specialization, and the others show stable specialization levels. Despite a few exceptions, a correlation between the level of regional specialization and the degree of sensitivity to economic disturbances can be observed. Regions that are less specialized and have more-diversified production structures show greater resistance to economic fluctuations. This is confirmed by the analysis of the morphology of cycles on a regional basis.